The Influence Of Drill, Small Game, And Agility Exercise Methods Against Dribbling Capability Of Students At PSB Junior Football School District XIII Koto Kampar - Syahrastani Syahrastani; Fajri Kamal (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
Multimedia is a more complex learning media, and a means of delivering messages in two or more forms. This study aims to determine the effect of 50 M freestyle swimming course using multimedia on the learning outcomes of student majoring in sports education at FIK UNP. The method used is quasi experiment. The sampling technique is done by using a random sample quota technique. The sample size for each treatment group is 10 people, so the number of samples is 20 people or 50% of the total population. The results of the data normality test calculation used the Kolmogorov Smirnov test at a significance level of 0.05, showing a significance value> 0.05, so that all sample groups in this study came from normally distributed populations. From the hypothesis test using the t test, tcount> ttable or significance ≤ α value (0.05) was produced. The conclusion of the study was the 50 M freestyle swimming course using multimedia significantly affected the learning outcomes of FIK UNP's Sport Education students.